Advanced development and mechanism of sepsis-related acute respiratory distress syndrome - Gong, Huankai; Chen, Yao; Chen, Meiling; Li, Jiankang; Zhang, Hong; Yan, Shijiao; Lv, Chuanzhu (Frontiers in Medicine, 2022)
The introduction of the Sepsis 3.0 guidelines in 2016 improved our understanding of sepsis diagnosis and therapy. Personalized treatment strategies and nursing methods for sepsis patients are recommended in the “Save Sepsis Campaign” in 2021. However, mortality in sepsis patients remains high. Patients with sepsis-related acute respiratory distress syndrome account for around 30% of them, with fatality rates ranging from 30 to 40%. Pathological specimens from individuals with sepsis-related ARDS frequently demonstrate widespread alveolar damage, and investigations have revealed that pulmonary epithelial and pulmonary endothelial injury is the underlying cause. As a result, the purpose of this work is to evaluate the mechanism and research progress of pulmonary epithelial and pulmonary endothelial damage in sepsis-related ARDS, which may provide new directions for future research, diagnosis, and therapy.